Current Control in Field-Excited Flux Switching Machines: No-Load Induced Voltage Impact Based on the Winding Connection - Diogo P. V. Galo; Thales A. C. Maia; Braz de J. Cardoso Filho (Eletrônica de Potência)
Micro and mild hybrid electric vehicles can make a significant contribution to reducing emissions and mitigating the environmental impact. Electric machine designs with fewer or no rare-earth permanent magnets will play an important role in the adoption of hybrid solutions. Doubly salient reluctance machines exhibit a simple structure, robust mechanical strength, excellent fault tolerance, and a wide range of speed regulation, which makes them suitable for in-wheel applications. Particular emphasis should be placed on flux-switching machines with wound-field excitation, which offer great operating flexibility, efficient heat dissipation, and power density of up to 4.8 kW/kg. This paper introduces a wound-field flux-switching machine designed for in-wheel applications, featuring individual field current control. The machine has individual access to each of the field coils. The primary objective of this research is to enhance the machine's operational versatility by enabling multiple configurations of the machine, adjusting the way the field-coils are connected. Firstly, a comparison of the armature no-load induced voltage is made for field coils connected in both series and parallel. Additionally, an assessment of the impact of open-circuit failures in one and two adjacent field coils is conducted. Finally, a current control strategy is proposed to effectively manage each individual field coil.